2021
DOI: 10.1136/annrheumdis-2021-220972
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence on “SARS-CoV-2 vaccination in rituximab-treated patients: evidence for impaired humoral but inducible cellular immune response” by Bonelli et al

Abstract: Provenance and peer review Not commissioned; internally peer reviewed. Supplemental material This content has been supplied by the author(s). It has not been vetted by BMJ Publishing Group Limited (BMJ) and may not have been peer-reviewed. Any opinions or recommendations discussed are solely those of the author(s) and are not endorsed by BMJ. BMJ disclaims all liability and responsibility arising from any reliance placed on the content. Where the content includes any translated material, BMJ does not warrant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
3
15
0
1
Order By: Relevance
“…The vast majority of included studies evaluated vaccines developed by Pfizer (BNT162b2) or Moderna (mRNA-1273). Thirteen studies included patients who received the vaccine developed by Janssen (Ad26.COV2.S) [ [25] , [26] , [27] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], nine included patients vaccinated with the AstraZeneca vaccine (ChAdOx1) [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], three included patients receiving the CoronaVac vaccine (Sinovac Biotech) [ [50] , [51] , [52] ], and one randomized controlled trial evaluated the vaccine developed by Novavax (NVX-CoV2373) vaccine [ 53 ]. One study included patients receiving the BBV152-Covaxin (Bharat Biotech) vaccine [ 44 ] and one included patients receiving the BBIBP-CorV (Sinopharm) vaccine [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of included studies evaluated vaccines developed by Pfizer (BNT162b2) or Moderna (mRNA-1273). Thirteen studies included patients who received the vaccine developed by Janssen (Ad26.COV2.S) [ [25] , [26] , [27] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], nine included patients vaccinated with the AstraZeneca vaccine (ChAdOx1) [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], three included patients receiving the CoronaVac vaccine (Sinovac Biotech) [ [50] , [51] , [52] ], and one randomized controlled trial evaluated the vaccine developed by Novavax (NVX-CoV2373) vaccine [ 53 ]. One study included patients receiving the BBV152-Covaxin (Bharat Biotech) vaccine [ 44 ] and one included patients receiving the BBIBP-CorV (Sinopharm) vaccine [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one studies reported immunogenicity in 4680 patients with inflammatory immune-mediated diseases ( Table S6 ) [ 27 , 28 , 32 , 36 , 37 , 39 , [45] , [46] , [47] , 50 , 51 , 54 , 55 , 82 , [161] , [162] , [163] , [164] , [165] , [166] , [167] , [168] , [169] , [170] , [171] , [172] , [173] , [174] , [175] , [176] , [177] , [178] ]. Main represented groups included rheumatoid arthritis ( n = 665), inflammatory bowel diseases ( n = 476) and multiple sclerosis ( n = 231).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with AAV receiving rituximab have been shown to have suboptimal response to the vaccine, with duration elapsed between rituximab and vaccine administration having a significant bearing on eventually developing antibodies. 4 It has been previously suggested that a delay in vaccine administration for at least 6 months post rituximab administration or B cell reconstitution should be considered to maximize efficacy of vaccines. 5 Another pertinent aspect that warrants discussion is the the immunogenicity of viral vector based COVID-19 vaccines.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In accordance with our series, the antibody response post viral vector COVID-19 vaccines may be suboptimal for immunocompromised patients as has been demonstrated in a previous study. 4 This finding does require more robust investigation to clarify which type of COVID-19 vaccine yields the most efficacious immune response.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…322 Nierentransplantierte) zeigten, dass 22 % nach Erst-sowie weitere 38 % nach Zweit-mRNA-1273-Impfung nachweisbare Antikörper hatten, während nur 8 % nach Erst-sowie weitere 40 % nach Zweit-BNT162b2-Impfung Antikörper entwickelten [8]. Bei 48 Patienten mit ANCA-assoziierter Vaskulitis, von denen 25 mRNA-1273, 19 BNT162b2 und 4 Ad26.COV2.S erhielten, konnten bei 14 (56 %), 4 (21,1 %) sowie 0 Patienten nach Impfung Antikörper nachgewiesen werden [9]. Die Höhe neutralisierender Antikörper, welche mit gemessenen Antikörpern gegen das Spike-Protein (häu-figster Antikörpernachweis) korrelieren, scheint mit einer Protektion vor symptomatischer Erkrankung assoziiert zu sein [10].…”
Section: Stand Der Dingeunclassified